Dynamical simulation of a four legged robot with shooting at targets using Fuzzy Logic Control - Tatar, Ahmet Burak; Tasar, Beyda; Tanyıldızı, Alper K.; Yakut, Oğuz (My University, 2024)
This study aims to track and shoot targets with a gun mounted on a quadruped robot in rough terrain and different environmental conditions for increase deterrence in defense. The dynamic movements of the system were modelled as planarly and it was used in walking movement. PID control was used for control the robot leg joints while walking. Because of the walking motion, the success of the target tracking and shooting simulations was examined under the disruptive effects. In order to track the targets whose coordinates were randomly determined and the elevation angle was calculated. It was observed that the robot tracked the targets at 3°, 6° and 9° with a maximum error of 0.6°. In addition, shootings were made to fixed targets located at 10 different coordinates. It was seen that the maximum shooting error value was 16 cm. So, this study will make important contributions to the defense industry.
Keywords: Fuzzy Control; Turret System; Four-Legged Robot; Barrel Stabilization; Shooting Simulation